PUBLIC POLICY AS A COMPONENT OF THE POLITICAL SYSTEM: CONCEPT AND CONCEPTUAL FIELD OF STUDY - Asiyat Kazievna Botasheva (Современная наука и инновации)
The state as the Central link of the political system has such a definite asset, as the government, which in all times and ages is the center of attention of various socio-political forces, the purpose of which is through gaining the power to dictate political and other will to the citizens, sometimes being with them in different dimensions: material and moral. To date, not always the activity of the state is able to cover itself in management functions and public policy, which makes the subject particularly topical.